2010
DOI: 10.1021/cm902972p
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Polyborazylene-Derived Bulk Boron Nitride with Tunable Properties by Warm-Pressing and Pressureless Pyrolysis

Abstract: The polymer-derived ceramics (PDCs) route has been combined with a warm-pressing process to synthesize for the first time boron nitride workpieces avoiding the conventional sintering process. A polyborazylene was synthesized with a controlled degree of cross-linking suitable to be warmpressed into cylindrical green bodies which were pressureless pyrolyzed into disk-shaped boron nitride workpieces. On the basis of elemental analyses, differential scanning calorimetry (DSC), and thermomechanical analyses (TMA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 44 publications
0
61
0
Order By: Relevance
“…[23][24][25][26] This method consists of the synthesis of a polymeric precursor, which is converted into ceramic after shaping. Among available precursors, recent works have shown that the use of polyborazylene (PBN) is the best alternative [27][28][29][30] because of its easy and reproducible synthesis, combined with its relatively high ceramic yield and high purity. Tailoring the condensation rate by altering the condensation time allows the polymer viscosity to be adjusted.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] This method consists of the synthesis of a polymeric precursor, which is converted into ceramic after shaping. Among available precursors, recent works have shown that the use of polyborazylene (PBN) is the best alternative [27][28][29][30] because of its easy and reproducible synthesis, combined with its relatively high ceramic yield and high purity. Tailoring the condensation rate by altering the condensation time allows the polymer viscosity to be adjusted.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting material, Boran carbide (B 4 C) can be synthesized by wet infi ltration technique [79]. As reported in literature, SBA-15 was infi ltrated with bisdecaboranyl-hexane precursor solution in ethanol and left overnight for evaporation.…”
Section: Nanocast Bivo 4 and B 4 Cmentioning
confidence: 99%
“…It has low temperature reducibility which is responsible for the excellent catalytic performance oxidation of typical volatile organic compounds such as formaldehyde, acetone, and methanol [78]. Cr 2 O 3 -PMA nanocomposites exhibit high catalytic activity and durability in oxidation of 1-phenylethanol using H 2 O 2 as an oxidant [79]. 5 wt.% mesoporous NiO milled together with MgH 2 shows faster H 2 desorption rates (7 times faster) together with slightly lower sorption activation energies compared with pure MgH 2 .…”
Section: Potential Applicationmentioning
confidence: 99%
“…Due to its high melting point, good thermal conductivity, high temperature stability and superior oxidation resistance, boron nitride (BN) has been a potential non-oxide ceramic material for aircraft and space applications [1,2]. The most promising approach for the fabrication of shaped BN such as fiber, film, and mesoporous material is polymer-derived ceramics (PDCs) method [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%